(untitled) (Baghdad Science Journal, 2015)
The study was preformed for investigating of Salmonella from meat, and compared Vidas UP Salmonella (SPT) with the traditional methods of isolation for Salmonella , were examined 42 meat samples (Beef and Chicken) from the Local and Imported From local markets in the city of Baghdad from period December 2013 -February 2014 the samples were cultured on enrichment and differential media and examined samples Vidas, and confirmed of isolates by cultivation chromgenic agar, biochemical tests ,Api20 E systeme , In addition serological tests , and the serotypes determinate in the Central Public Health Laboratory / National Institute of Salmonella The results showed the contamination in imported meat was more than in the local meat 11.9% and 2.3 %, respectively, also recorded the highest isolation of Salmonella from chicken meat compared with beef meat 9.5% and 4.7%, respectively, where isolated 3 serotype (7.14%) from imported chicken meat include S.typhimurium S.entertidis and S.livingstone at16.6% for each of them and 1 serotype (2.3%) isolate from local chicken meat include S.hadar 16.6%. The study recorded for the first time isolate of S. living stone in Iraq from imported chicken. While isolated 2 serotype (4.7%) isolate from imported beef included S. dublin and S. antum at 16.6% each of them .the sensitivity of antibiotics , was studies the results showed that it was resistant to each of Trimethprime Cetazidime Ampicillin Chloromphenicol, Ceftriaxone, and Amoxicillin (100, 66.6 ,33.3, 16.6 , 16.6 , and 16.6 ) % respectively , but sensitivite to Imipenem and Ciprofloxacin at 100% and confirmed the results that the Vidas technique better than traditional methods for speed and accuracy of their results.